2017
DOI: 10.3892/mco.2017.1348
|View full text |Cite
|
Sign up to set email alerts
|

A case-control study of the association between psychosocial factors and the occurrence of laryngeal cancer

Abstract: Abstract. The aim of the present study was to investigate the association between social psychological factors and the occurrence of laryngeal cancer. A 1:1 matched case-control study was conducted. The participants completed questionnaires that included general information, such as the Life Event Scale, the Social Support Rating Scale, and the Eysenck Personality Questionnaire (EPQ). Scores were compared between the groups using paired t-tests and Wilcoxon's signed-rank tests. No significant difference in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 32 publications
0
8
0
Order By: Relevance
“…Social support is considered to promote biological or behavioural adaptations under conditions of stress. This may result in better treatment compliance and the adoption of better health behaviours, which will generally exert positive effects on overall physical condition 54. Several studies have also described how the patient’s concealment of symptoms may influence the delay in seeking medical, while discussing them with friends and family can facilitate the decision to seek medical advice 55…”
Section: Discussionmentioning
confidence: 99%
“…Social support is considered to promote biological or behavioural adaptations under conditions of stress. This may result in better treatment compliance and the adoption of better health behaviours, which will generally exert positive effects on overall physical condition 54. Several studies have also described how the patient’s concealment of symptoms may influence the delay in seeking medical, while discussing them with friends and family can facilitate the decision to seek medical advice 55…”
Section: Discussionmentioning
confidence: 99%
“…Social support is considered to promote biological or behavioral adaptations under conditions of stress. Low social support may lead to mood disturbance (Åhlin et al, 2018 ), worse treatment compliance (Sousa et al, 2019 ), and unhealthy behaviors, which usually have a negative impact on the overall physical condition (Wang et al, 2017 ). In accord with previous studies, lack of social support was found as an important element for prehospital delay (Reisinger et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…The LES evaluates 48 common life events in China regarding family, occupational, academic and social communication domains. A higher LES score indicates greater psychological stress 36. The LES was designed specifically for Chinese people and has good inter-rater reliability and internal consistency 37.…”
Section: Methods and Analysismentioning
confidence: 99%
“…A higher LES score indicates greater psychological stress. 36 The LES was designed specifically for Chinese people and has good inter-rater reliability and internal consistency. 37 These three assessments will also be administered at baseline and every 6 months.…”
Section: Data Collection Proceduresmentioning
confidence: 99%